Longitudinal increase in vitamin D binding protein levels after initiation of tenofovir/lamivudine/efavirenz among individuals with HIV. (31st July 2016) - Hsieh, Evelyn; Fraenkel, Liana; Han, Yang; Xia, Weibo; Insogna, Karl L.; Yin, Michael T.; Zhu, Ting; Cheng, Xinqi; Li, Taisheng
Abstract : Objective: To examine longitudinal change in vitamin D binding protein (DBP) levels during the first year after initiation of tenofovir disoproxil fumarate (TDF)/lamivudine/efavirenz and compare these findings with concurrent changes in markers of skeletal metabolism. Design: Secondary analysis of plasma samples collected from an ongoing multicenter clinical trial. Methods: Plasma samples collected at 0, 24, and 48 weeks after initiation of TDF + lamivudine + efavirenz from 134 adult participants enrolled in a multicenter randomized trial were analyzed. Data regarding sociodemographic and clinical characteristics were obtained as part of the parent study. Laboratory analyses included plasma DBP, intact parathyroid hormone, total 25-hydroxy vitamin D, phosphorus, the bone resorption marker collagen type 1 cross-linked C-telopeptide, and the bone formation marker total procollagen type 1 N-terminal propeptide. Repeated measures analysis of variance was used to measure changes in biomarkers over time. Results: Our sample included 108 men and 26 women (mean age 33.6 ± 9.6 years). Median levels of DBP increased significantly from baseline to 48 weeks [154 (91.8–257.4) versus 198.3 (119.6–351.9) μg/ml, P  < 0.001]. A concurrent rise in intact parathyroid hormone levels was observed over the same period [32.3 (24.4–40.9) versus 45.2 (35.1–60.4) pg/ml, P  < 0.001]; however, 25-hydroxy vitamin D and phosphorus levels remained stable. Bone resorption and formation markers rapidly increased from 0 to 24 weeks, followed by a slight decline or plateau, but remained significantly elevated at 48 weeks ( P  < 0.001). Conclusion: Our study provides longitudinal data supporting a potential role for DBP in bone loss associated with TDF-based therapy. Further research to elucidate the mechanistic pathways and clinical impact of these findings is warranted.